Comparison of Morphometric Variation of Ramus Length and Mandibular Corpus Length in Patients at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia, Based on Gender - Muzakkie, Mufida; Muhammad Febriandi Djunaidi; S.N.A Ratna Sari Devi; Ziske Maritska (Sriwijaya Journal of Surgery, 2023)
Introduction: Planned mandibular reconstruction with the help of morphometry allows plastic surgeons to perform operations with greater precision. They can plan bone shifts and cuts more accurately, minimize damage to surrounding tissue, and achieve cosmetically and functionally better results. This study aimed to compare the morphometric variation of ramus length and mandibular corpus length in patients at Dr. Mohammad Hoesin General Hospital, Palembang, Indonesia, based on gender. Methods: This study was a cross-sectional analytic observational study. A total of 96 research subjects participated in this study, where the length of the ramus and corpus of the mandibular was obtained by assessing the 3D CT scan of the mandibular. Data analysis was carried out using SPSS in a bivariate. Results: The length of the mandibular ramus dextra and sinistra shows that the male gender is longer than the female gender, where the p-values are 0.000 and 0.001, respectively (p<0.05). The length of the mandibular corpus dextra and sinistra did not show a statistical difference in length, where the p-value was > 0.05. Conclusion: There is a difference in the length of the mandibular ramus between men and women, but there is no significant difference between the length of the corpus mandibular between men and women.